Risk factors for cardiovascular disease among the homeless and in the general population of the city of Porto, Portugal Fatores de risco cardiovascular em pessoas sem-abrigo e na população geral da cidade do Porto, Portugal - Luis de Pinho Oliveira; Maria Lurdes Pereira; Ana Azevedo; Nuno Lunet (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
We described the distribution of risk factors for cardiovascular disease among homeless people living in the city of Porto, Portugal. Comparisons were made between subsamples of homeless people recruited in different settings and between the overall homeless sample group and a sample of the general population. All "houseless" individuals attending one of two homeless hostels or two institutions providing meal programs on specific days were invited to participate and were matched with subjects from the general population. We estimated sex, age and education-adjusted prevalence ratios or mean differences. The prevalence of previous illicit drug consumption and imprisonment was almost twice as high among the homeless from institutions providing meal programs. This group also showed lower mean systolic and diastolic blood pressure. Prevalence of smoking was almost 50% higher in the overall homeless group. Mean body mass index and waist circumference were also lower in the homeless group and its members were almost five times less likely to report dyslipidemia. Our findings contribute to defining priorities for interventions directed at this segment of society and to reducing inequalities in this extremely underprivileged population. Este estudo descreve a distribuição de fatores de risco cardiovascular em pessoas sem-abrigo que vivem no Porto, Portugal, recrutadas em diferentes contextos, comparando-as entre si e com a população em geral. Todos os indivíduos "sem-casa" presentes em dois albergues de sem-abrigo ou dois refeitórios sociais em dias selecionados para as avaliações foram convidados, e emparelhados com indivíduos da população geral. Foram estimadas as razões de proporções ou diferenças entre médias, ajustadas para sexo, idade e educação. Nos refeitórios sociais, observou-se maior prevalência de consumo de drogas ilícitas e de história prévia de prisão no último ano, e menor pressão arterial sistólica e diastólica do que nos albergues de sem-abrigo. Os sem-abrigo apresentaram uma prevalência quase 50% maior de fumadores, menor índice de massa corporal e perímetro da cintura, e uma probabilidade 5 vezes menor de referir dislipidemia. Este trabalho contribui para a definição de prioridades de intervenção para a redução de desigualdades sociais nessas populações com extremas carências socioeconômicas.